System information accounting in business performance: A systematic literature review - Maulina, Baiq Farida; Nazaruddin, Ietje (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research Aims: This study evaluates journals discussing the impact of Accounting Information Systems (AIS) on Business Performance to derive useful lessons for addressing future challenges.Design/Methodology/Approach: Using a review framework adapted from Hoque (2014), this study analyzes 58 journals selected through a keyword search (